Analisis Kebijakan Sertifikasi dalam Peningkatan Kinerja Tenaga Pendidik di SMK Sunan Drajat Lamongan - Miftachul Ulum; Abdul Mun'im (Mu'allim, 2022)
Success in teaching and learning activities in an educational institution environment is largely determined by education staff or teachers. Educators make one of the realizations of the quality of education in schools for the better. The professionalism of a teacher is one of the determinants that the process of learning activities goes well and perfectly. The teacher's role is part of the strategy in determining the quality of students. This study describes a policy of certification in improving the performance of educators. Understanding of educators in certification policies. Indicators in improving the performance of educators. This research was conducted on certified educators at SMK Sunan Drajat Lamongan. Information that has been obtained from 43 certified teachers states that the understanding of policies on certification is very good, the understanding of implementation for teachers is very understanding and very good in understanding. The requirements and implementation process during certification activities are very well understood. The understanding of the purpose of certification is very well understood. In the implementation of certification, educators have competencies that include pedagogic competence, professional competence, personality competence and social competence